Predictors of iron levels in 14, 737 Danish blood donors: results from the Danish Blood Donor Study. Issue 3 (23rd December 2013) - Rigas, Andreas Stribolt; Sørensen, Cecilie Juul; Pedersen, Ole Birger; Petersen, Mikkel Steen; Thørner, Lise Wegner; Kotzé, Sebastian; Sørensen, Erik; Magnussen, Karin; Rostgaard, Klaus; Erikstrup, Christian; Ullum, Henrik
Abstract : Background: Dietary studies show a relationship between the intake of iron enhancers and inhibitors and iron stores in the general population. However, the impact of dietary factors on the iron stores of blood donors, whose iron status is affected by blood donations, is incompletely understood. Study Design and Methods: In the Danish Blood Donor Study, we assessed the effect of blood donation frequency, physiologic factors, lifestyle and supplemental factors, and dietary factors on ferritin levels. We used multiple linear and logistic regression analyses stratified by sex and menopausal status. Results: Among high‐frequency donors (more than nine donations in the past 3 years), we found iron deficiency (ferritin below 15 ng/mL) in 9, 39, and 22% of men, premenopausal women, and postmenopausal women, respectively. The strongest predictors of iron deficiency were sex, menopausal status, the number of blood donations in a 3‐year period, and the time since last donation. Other significant factors included weight, age, intensity of menstruation, iron tablets, vitamin pills, and consumption of meat and wine. Conclusion: The study confirms iron deficiency as an important problem, especially among menstruating women donating frequently. The risk of iron depletion was largely explained by sex, menopausal status, and donation frequency. Other factors, including dietary and supplemental iron intake, had a much weaker effect on the risk of iron depletion.